Comparative study of four advanced 3d-conformal radiation therapy treatment planning techniques for head and neck cancer - Mohamed Yassine Herrassi; Farida Bentayeb; Maria Rosa Malisan (Journal of Medical Physics, 2013)
For the head-and-neck cancer bilateral irradiation, intensity-modulated radiation therapy (IMRT) is the most reported technique as it enables both target dose coverage and organ-at-risk (OAR) sparing. However, during the last 20 years, three-dimensional conformal radiotherapy (3DCRT) techniques have been introduced, which are tailored to improve the classic shrinking field technique, as regards both planning target volume (PTV) dose conformality and sparing of OAR′s, such as parotid glands and spinal cord. In this study, we tested experimentally in a sample of 13 patients, four of these advanced 3DCRT techniques, all using photon beams only and a unique isocentre, namely Bellinzona, Forward-Planned Multisegments (FPMS), ConPas, and field-in-field (FIF) techniques. Statistical analysis of the main dosimetric parameters of PTV and OAR′s DVH′s as well as of homogeneity and conformity indexes was carried out in order to compare the performance of each technique. The results show that the PTV dose coverage is adequate for all the techniques, with the FPMS techniques providing the highest value for D95%; on the other hand, the best sparing of parotid glands is achieved using the FIF and ConPas techniques, with a mean dose of 26 Gy to parotid glands for a PTV prescription dose of 54 Gy. After taking into account both PTV coverage and parotid sparing, the best global performance was achieved by the FIF technique with results comparable to that of IMRT plans. This technique can be proposed as a valid alternative when IMRT equipment is not available or patient is not suitable for IMRT treatment.